2016
DOI: 10.1016/j.postcomstud.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

We hate them all? Issue adaptation of extreme right parties in Slovakia 1993–2016

Abstract: This article presents electoral developments and mobilization issues of the extreme right political parties between 1993 and 2016. It analyzes the changes in the extreme right discourses and framing strategies in relation to their electoral results. We argue that during the transition to democracy in the 1990s and partially later in the 2000s, the extreme right parties were predominantly focusing on the issues related to national sovereignty and were successful mostly in the context of hostility against groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 23 publications
0
22
0
2
Order By: Relevance
“…It has been represented in parliament continuously from 1990 to the present (apart from 2002-6 and 2012-16). 67 It had already adopted an anti-Muslim agenda in 2010 when it joined the protest against the mosque in the Czech city of Brno. 68 The SNS has issued several anti-Islamic proclamations that warn of an 'Islamization of Europe' and the introduction of sharia in Slovakia.…”
Section: Islamophobic Populism In Visegrád Four Party Politicsmentioning
confidence: 99%
“…It has been represented in parliament continuously from 1990 to the present (apart from 2002-6 and 2012-16). 67 It had already adopted an anti-Muslim agenda in 2010 when it joined the protest against the mosque in the Czech city of Brno. 68 The SNS has issued several anti-Islamic proclamations that warn of an 'Islamization of Europe' and the introduction of sharia in Slovakia.…”
Section: Islamophobic Populism In Visegrád Four Party Politicsmentioning
confidence: 99%
“…Populist and radical right-wing parties have augmented their public appeal, embedding staunch opposition to minority rights and immigration into the broader frame of their Eurosceptic agendas (e.g. the cases of Estonia, Latvia, Slovakia and Hungary) (Kasekamp, Madison, & Wierenga, 2018;Kluknavská & Smolik, 2016;Kovarek, Róna, Hunyadi, & Krekó, 2017;Braghiroli & Petsinis, 2019). Furthermore, EU-membership has lost much of its attraction among candidate states in the region (e.g.…”
mentioning
confidence: 99%
“…By quantifying the data like this we are able to show that gender issues are only a periphery theme for the ĽSNS and do not form the core of its ideological programme. Kluknavská and Smolík (2016) have shown that far right parties in Slovakia prioritised nationalist, populist and xenophobic appeals with a discourse aimed largely against the Roma and more recently immigrants. Women as mothers of the nation whose main role is to look after the child and family, men as the family breadwinner.…”
Section: Resultsmentioning
confidence: 99%